Editorial (2017)
Journals tend to be regional in the sense that their readership usually focuses on its own personal scope. For instance, it is hard to find a truly international journal with papers from many different countries. However, this time Profile journal has made a major effort to obtain valuable contributions from beyond the South American continent. In fact, this special issue brings together a number of very appealing topics which reflect on a common tendency. There is a clear orientation towards technology-based language teaching which can be seen in many parts of the world.